2020
DOI: 10.1055/a-1128-0421
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Aldosterone-Producing Cell Clusters in Adrenal Disease

Abstract: Primary aldosteronism (PA) is the most common cause of secondary hypertension. The hallmark of PA is adrenal production of aldosterone under suppressed renin conditions. PA subtypes include adrenal unilateral and bilateral hyperaldosteronism. Considerable progress has been made in defining the role for somatic gene mutations in aldosterone-producing adenomas (APA) as the primary cause of unilateral PA. This incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
(121 reference statements)
3
10
0
Order By: Relevance
“…Similarly, a recent study using tandem mass spectrometry imaging verified Suguira et al’s findings in normal adrenals as elevated levels of aldosterone and 18-oxocortisol were found in APCC’s relative to the adjacent adrenal tissue in an adrenal obtained from a patient that had undergone radical nephrectomy for renal cell carcinoma ( 51 ). These studies support the steroidogenic activity of APCCs in producing aldosterone in normal adrenals as well as under suppressed renin conditions, as shown in PA patients’ adrenals ( 44 ). Accordingly, APCCs has been proposed to be the transitioning step to APAs ( 50 ).…”
Section: Significance Of Apccs To Age-related Hypertensionsupporting
confidence: 85%
See 3 more Smart Citations
“…Similarly, a recent study using tandem mass spectrometry imaging verified Suguira et al’s findings in normal adrenals as elevated levels of aldosterone and 18-oxocortisol were found in APCC’s relative to the adjacent adrenal tissue in an adrenal obtained from a patient that had undergone radical nephrectomy for renal cell carcinoma ( 51 ). These studies support the steroidogenic activity of APCCs in producing aldosterone in normal adrenals as well as under suppressed renin conditions, as shown in PA patients’ adrenals ( 44 ). Accordingly, APCCs has been proposed to be the transitioning step to APAs ( 50 ).…”
Section: Significance Of Apccs To Age-related Hypertensionsupporting
confidence: 85%
“…IHC analysis has shown that compared to ZF cells that are generally negative for CYP11B2 and unrelated to aldosterone production, ZF-like looking cells of APCCs in the ZF has high levels of CYP11B2 and low levels of CYP11B1 or CYP17A1, both enzymes being involved in cortisol production ( 33 , 35 , 37 , 38 ). However, according to Lim & Rainey ( 44 ), APCCs may manifest various patterns of enzyme expression with some exhibiting homogeneous expression of CYP11B2 while others exhibit polarity with a declining expression of CYP11B2 aligned with the development of CYP17A1 expression. This pattern of expression indicates that some APCCs cells may go through a transition to a more ZF-like phenotype, at least partially ( 44 ), thus making CYP11B1 and CYP17A1 IHC useful to characterize APCCs ( 33 , 35 ).…”
Section: Characteristics Of Aldosterone-producing Cell Clusters (Apccmentioning
confidence: 99%
See 2 more Smart Citations
“…In an original publication, Handgriff et al analyze the association between glucocorticoid co-secretion, assessed by the 1 mg dexamethasone suppression test, on the prevalence and the time course of thyroid antibodies in PA [13]. In a series of pathophysiologic manuscripts, the role of mast cells [14], expression of aldosterone synthase in adrenalectomy samples [15], the role of aldosterone producing cell clusters [16], and the methodologic advances obtained by tissue mass spectrometry imaging [17] are analyzed. Finally, the study of Gao et al [18] gives a comprehensive overview on calcium metabolism in PA, followed by an in-depth study on clinical determinants of surgical success by Naruse et al [19].…”
mentioning
confidence: 99%